Sprawozdanie z międzynarodowej konferencji naukowej nt. "Przyrodoznawstwo – Filozofia – Teologia. Obszary i perspektywy dialogu", Uniwersytet Kardynała Stefana Wyszyńskiego, Warszawa, 15–16 października 2019 r. - Andrzej Kobyliński (Studia Philosophiae Christianae)
On October 15-16, 2019, an international interdisciplinary conference "Science - Philosophy - Theology. Dialogue areas and perspectives" was held at the Cardinal Stefan Wyszyński University in Warsaw. Over twenty scientists from ten countries participated in the conference.